Spotkanie naukowe historyków wychowania przedszkolnego Bamberg (RFN) 9-12.09.1995 r. - Hellwig, Jan (Biuletyn Historii Wychowania, 1996)
Spotkanie naukowe historyków wychowania przedszkolnego Bamberg (RFN) 9-12.09.1995 r.